Poster Presentations 2017
DOI: 10.1136/annrheumdis-2017-eular.6835
|View full text |Cite
|
Sign up to set email alerts
|

THU0424 Gout at the spine: a retrospective study with dual-energy computed tomography

Abstract: BackgroundGout is due to monosodium urate (MSU) crystal deposition after chronic hyperuricemia. Although MSU crystal deposition can occur in every joint and peri-articular structure, spine involvement is scarcely reported. Dual energy computed tomography (DECT) is a performant tool to assess urate deposits, especially in deep structures such as intervertebral discs and apophyseal joints.Objectivesto describe spinal DECT features of urate monosodium deposits compared to peripheral joint DECT.MethodsPatient with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…DECT has recently been used to accurately detect MSU crystals throughout the spine [ 52 ] ( Figure 3 D–F). A retrospective analysis of DECT examinations in gout patients found spinal urate deposition in 60% of scans (in 83% of symptomatic, and 25% of asymptomatic cases) [ 53 ]. Another prospective study of the lumbosacral spine showed gout patients had significantly higher volumes of spinal MSU deposits compared to non-gout controls and the volume of spinal MSU deposits was proportional to sUA levels [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…DECT has recently been used to accurately detect MSU crystals throughout the spine [ 52 ] ( Figure 3 D–F). A retrospective analysis of DECT examinations in gout patients found spinal urate deposition in 60% of scans (in 83% of symptomatic, and 25% of asymptomatic cases) [ 53 ]. Another prospective study of the lumbosacral spine showed gout patients had significantly higher volumes of spinal MSU deposits compared to non-gout controls and the volume of spinal MSU deposits was proportional to sUA levels [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Findings on MRIs can be quite variable and nonspecific because tophaceous lesions can appear hypointense or isointense on soft tissue densities on T1 and can range from hypointense to hyperintense on T2 images (1,7,15,24). Recently, newer methods of imaging gout with dualenergy CT (DECT) scanning is being developed (25,26). DECT can differentiate different materials based on their relative absorption of X-rays at different photon energy levels (25,27).…”
Section: Discussionmentioning
confidence: 99%
“…DECT can differentiate different materials based on their relative absorption of X-rays at different photon energy levels (25,27). There are currently a few promising cases of using DECT in the work up of spinal gout patients (26,28,29). In the absence of DECT, Hou et al presents an algorithm that helps in the diagnosis and management of presumed spinal gout (2).…”
Section: Discussionmentioning
confidence: 99%
“…Application of DECT imaging may avoid surgery and hospitalization (68,69) in gout patients with symptomatic spinal manifestation. Chotard et al showed in their retrospective study on gout subjects that 60% DECT of these subjects had urate deposits in the spine out of which 83% were symptomatic (70). A study done by Anastasia S et al found that gout patients had higher rate and severity of back pain as compared to control subjects.…”
Section: Msu Deposition In Spinementioning
confidence: 98%